Mapping religion and spirituality in a postsecular world - Giordan, Giuseppe.; Pace, Enzo. (Religion and the Social Order, 2012)
Individualization of believing and the logic of pluralism today inevitably bring a redefinition of the role of religion in the lives of individuals as well as societies themselves. New concepts and new theories are necessary to try to describe and understand how such processes work: this is without doubt the most problematic and intriguing aspect of the processes of change that characterize our era. This is a difficulty that makes us use only partially, and often with much caution, words, concepts and theories that until not long ago had a convincing heuristic and explanatory power and were, at least apparently, indisputable. Once it is established that under the sacred vaults of religion nothing is created and nothing is destroyed, but everything is preserved and transformed, what are the connections that are now being established with the sacred in society? The concepts "spirituality" and "post-secular" give important insights into the new religious landscape.